1983
DOI: 10.1002/1097-0142(19830815)52:4<707::aid-cncr2820520424>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal cortical carcinoma a study of 77 cases

Abstract: Seventy‐seven patients with histologically proven adrenal cortical carcinoma seen at the University of Texas M. D. Anderson Hospital (1950–1981) were studied. Thirty‐nine were women (mean age at diagnosis, 36.6 years), and 38 were men (mean age at diagnosis, 48.3 years). On presentation, 41 of 74 had abdominal symptoms (55.4%) and 25 of 74 had an abdominal mass (33.8%). Twenty‐six patients (33.8%) were found to have clinically functional disease (18 women, 8 men). At diagnosis, 26 (33.8%) had clinical or radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
2
4

Year Published

1987
1987
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(88 citation statements)
references
References 10 publications
8
74
2
4
Order By: Relevance
“…18,19 Patient 2, with anaplastic thyroid carcinoma, was diagnosed at age 39 years; the average age of diagnosis for this tumor is 66.5 years. 20 The early age of onset for both of these patients is again highly suggestive that these tumors were related to the underlying MSH2 defect and not coincidental.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Patient 2, with anaplastic thyroid carcinoma, was diagnosed at age 39 years; the average age of diagnosis for this tumor is 66.5 years. 20 The early age of onset for both of these patients is again highly suggestive that these tumors were related to the underlying MSH2 defect and not coincidental.…”
Section: Discussionmentioning
confidence: 99%
“…This malignancy represents approximately 0.02% of all cancers (1,2) and within the general population occurs with a frequency of about two cases per million individuals per year (3). Nearly two-thirds of diagnosed patients are women.…”
Section: Introductionmentioning
confidence: 99%
“…6 Although early studies in the era before modern imaging modalities reported high response rates, it now is clear that mitotane has at best a 19 -22% response rate. [7][8][9] In addition to the evaluation of mitotane, numerous studies examining the efficacy of conventional chemotherapy have demonstrated either no or very low activity, indicating a limited role for these agents. 10 -12 Doxorubicin as a single agent or in combination chemotherapy has shown some activity against ACC.…”
mentioning
confidence: 99%